Noetics in pastoral counselling: The making of a semantic differential analysis in pastoral care and counselling - Louw, Dani J. (Verbum et ecclesia, 2011)
Praxis in pastoral care and counselling entails more than merely practice and practicalities (communication skills). Praxis refers to the intentionality within human action and behaviour. Praxis exhibits the realm of intentionality and meaning as displayed within and by human attitudes. It is hypothesised that due to the noetic dimension in human actions, the making of a pastoral diagnosis (a qualitative assessment of the impact of Christian spirituality and the meaning on the system of existential, relational networking) should deal with the realm of significant and purposeful intentionality. The latter is already implied in the phenomenological approach of Edmund Husserl’s eidetic observation or inspection (phenomenological consciousness). In order to incorporate noetics in pastoral care and counselling, a pastoral semantic differential analysis (PSDA) within the making of a pastoral diagnosis was proposed. The PSDA was linked to the need for a qualitative approach regarding the impact of Godimages on religious association and existential life experiences.